Transfer kwot mlecznych bez gospodarstwa w prawie polskim - Bobeł, Łukasz (Wydawnictwo Naukowe UAM, 2007)
The subject o f this paper is the regulation governing exclusive transfer o f milk quotas without the transfer o f the holding as provided for in Polish law. The term “transfer o f milk quota” contained in the title o f the paper is used in its broad sense. It covers both the disposal o f the quota (definitive transfer) and the granting o f the right to use the quota (temporary transfer). The system o f the milk quota transfer chosen by Poland does not rely on the strict, inseparable link between the quota and the holding. Moreover, it works in only one direction. This means that the disposal of, or the granting o f a right to use holding entails the transfer o f quota as well, while in order to transfer the quota only, it is not necessary to dispose o f the holding or grant the right to use it. Thus, it is possible to transfer the milk quota definitively or temporarily without the transfer o f or granting the right to use the holding. However, transactions involving the disposal o f a holding or granting the right to use the holding, need to comply with the requirements imposed by the legislator. The purpose o f the paper is to resolve selected issues arising from the application of the provisions on the transfer o f quotas without the transfer o f the holding in practice. There are numerous problems and they often result from the absence o f clear regulations and the necessity to apply complex methods o f interpretation. Some o f the common problems are o f special importance to farmers and have already become the subject o f various administrative courts decisions.
TRANSFER OF MILK QUOTAS WITHOUT THE TRANSFER OF THE HOLDING UNDER POLISH LAW